2012
DOI: 10.1007/s00296-012-2536-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of TLR4 gene non-missense single nucleotide polymorphisms with rheumatoid arthritis in Chinese Han population

Abstract: Toll-like receptor4 (TLR4) plays an important role in the induction and regulation of the innate or adaptive immune responses. Thus, the genetic variation in TLR4 gene may influence the development of autoimmune diseases such as rheumatoid arthritis (RA). Several studies have investigated the roles of genetic polymorphisms of TLR4 gene in RA, but most of these studies were restricted to two cosegregating functional missense polymorphisms Asp299Gly and Thr399Ile. To determine whether non-missense genetic polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“… 50 , 64 66 The −1607C allele may be a risk factor for prostate cancer 47 and traffic-related air pollution-associated childhood asthma, 51 and the +12186C allele may be a risk factor for rheumatoid arthritis. 56 However, none of these studies looked into the possible mechanisms of these allelic associations. In female genital epithelial cells, TLR4 binds to HIV-1 gp120 and triggers pro-inflammatory cytokine production via activation of NF-kB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 50 , 64 66 The −1607C allele may be a risk factor for prostate cancer 47 and traffic-related air pollution-associated childhood asthma, 51 and the +12186C allele may be a risk factor for rheumatoid arthritis. 56 However, none of these studies looked into the possible mechanisms of these allelic associations. In female genital epithelial cells, TLR4 binds to HIV-1 gp120 and triggers pro-inflammatory cytokine production via activation of NF-kB.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 45 SNPs in 8 TLR genes ( TLR1 , 2 , 3 , 4 , 6 , 7 , 8 , and 9 ), which have been evaluated in HIV/AIDS 28 35 and other infectious 36 45 as well as inflammatory and immune-mediated non-infectious 46 56 diseases, were included in the present study. These SNPs were located in promoter regions, 5′-UTRs, exons, introns, and 3′-UTRs ( Supplementary Table A ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, limited population-based genetic studies have demonstrated that the polymorphism loci of rs41426344, rs7873784, and rs11536891 are associated with the risk of rheumatoid arthritis and juvenile idiopathic arthritis [9,10], IgA nephropathy [6], and bipolar disorder [7]. In contrast, the luciferase activities of constructs corresponding to these variations produced almost constant levels of luciferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the dbSNP database revealed 669 SNPs in the TLR4 3'-UTR (http://www.ncbi.nlm.nih.gov/SNP/). Only six of these SNPs (rs41426344, rs7869402, rs11536889, rs7873784, rs11536891, and rs11536896) had been analyzed in specific populations using case-control studies [6][7][8][9][10][11][12]. Of these SNPs, rs11536889 is the most extensively studied.…”
mentioning
confidence: 99%